Prevalence of depression among young people with Type 1 diabetes: a systematic review. Issue 2 (21st January 2013) - Johnson, B.; Eiser, C.; Young, V.; Brierley, S.; Heller, S.
<x xml:space="preserve">Abstract</x> Diabet. Med. 30, 199–208 (2013) Abstract Aims To determine: (1) prevalence of depression among young people with Type 1 diabetes compared with control groups or population norms; (2) implications of depression for HbA1c level; and (3) the relationship between history of depressive symptoms and future depressive symptoms. Background Among adults with Type 1 diabetes depression is higher than the general population, and has been associated with adverse implications for self‐care and HbA1c level. The last published review of depression among young people with Type 1 diabetes only included studies up to 1999. Method Systematic searches were conducted for articles published from January 1999 to December 2011 including young people (up to 25 years old) with Type 1 diabetes. Results Twenty‐three articles met the inclusion criteria. Of five studies that reported prevalence of depression compared with control groups, three found no differences. Of the three studies that investigated prevalence of depression making reference to population norms, all three showed higher rates of depressive symptoms. Fourteen of 15 studies found associations between more depressive symptoms and higher HbA1c level either cross‐sectionally or longitudinally. Past depressive symptoms were associated with later depressive symptoms. Conclusions Current evidence is inconclusive about whether there is increased prevalence of depression among young adults with Type 1 diabetes, as established among adults, but those who are more depressed have higher HbA1c level. This review is limited by methodological problems and no identified work in the UK met the inclusion criteria. Given the adverse clinical outcomes, we conclude there is a case for routine mental health screening for young adults with Type 1 diabetes.